Climate smart agriculture multistakeholder platform strategic plan 2022-2026 - Makokha, Jeff; Waswa, Canute (Kenya Climate Smart Agriculture Multi Stakeholder Platform, 2022)
Addressing climate change impacts in agriculture is a collective responsibility of all stakeholders in the sector. The ministry has identified Climate Smart Agriculture (CSA) as a viable approach to provide solutions towards increased agriculture productivity while addressing impacts of the changing climate. CSA provides the means to help stakeholders at local, national and international levels to identify agricultural strategies suitable to their conditions. Sector stakeholders need to play their respective roles in ensuring this approach is successfully implemented to guarantee continued sector growth while shielding it from the negative impacts of climate change. This Five-Year Strategic Plan (FYSP) has been developed to provide strategic direction and guide the programmes of the Climate Smart Agriculture Multi-Stakeholder Platform (CSA MSP) from 2022 to 2026.